De zingeving van Henri Matisse - ter Borg, Meerten (Religie & Samenleving, 2013)
People are constantly communicating their definition of reality, in face-to-face interactions as well as in indirect forms of communication such as art. This also holds for the ultimate meaning of life, death and suffering. Several works of Henri Matisse, notably in the chapel at Vence, shed light on aspects of this process of sense giving. Grounded in everyday life his art rises to the realm of ultimate meaning, giving the artist a means of transcending his own suffering.